Step-by-step explanation:
Part A:
can be written as the square of u³, or
. Similarly,
. Hence, we can write this as a difference of two squares by writing it as
![(u^3)^2-(v^3)^2](https://tex.z-dn.net/?f=%28u%5E3%29%5E2-%28v%5E3%29%5E2)
Part B:
<h3>Difference of Two Squares</h3>
<u>We can first factor a difference of two squares a² - b² into </u><u>(a+b)(a-b)</u>. Here, <em>a</em> would be u³ and <em>b</em> would be v³.
![(u^3+v^3)(u^3-v^3)](https://tex.z-dn.net/?f=%28u%5E3%2Bv%5E3%29%28u%5E3-v%5E3%29)
<h3>Sum and Difference of Two Cubes</h3>
We can factor this further by the use of two special formulas to factor a sum of two cubes and a difference of two cubes. These formulas are as follows:
![a^3+b^3=(a+b)(a^2-ab+b^2)\\a^3-b^3=(a-b)(a^2+ab+b^2)](https://tex.z-dn.net/?f=a%5E3%2Bb%5E3%3D%28a%2Bb%29%28a%5E2-ab%2Bb%5E2%29%5C%5Ca%5E3-b%5E3%3D%28a-b%29%28a%5E2%2Bab%2Bb%5E2%29)
Since u³ + v³ is a sum of two cubes, let's rewrite it.
![u^3+v^3=(u+v)(u^2-uv+v^2)](https://tex.z-dn.net/?f=u%5E3%2Bv%5E3%3D%28u%2Bv%29%28u%5E2-uv%2Bv%5E2%29)
Since u³ - v³ is a difference of two cubes, we can rewrite it as well.
![u^3-v^3=(u-v)(u^2+uv+v^2)](https://tex.z-dn.net/?f=u%5E3-v%5E3%3D%28u-v%29%28u%5E2%2Buv%2Bv%5E2%29)
Now, let's multiply them together again to get the final factored form.
![u^6-v^6=(u+v)(u^2-uv+v^2)(u-v)(u^2+uv+v^2)](https://tex.z-dn.net/?f=u%5E6-v%5E6%3D%28u%2Bv%29%28u%5E2-uv%2Bv%5E2%29%28u-v%29%28u%5E2%2Buv%2Bv%5E2%29)
Part C:
If we want to factor
completely, we can just see that x to the sixth power is just
and 1 to the sixth power is just 1. Hence, x can substitute for <em>u </em>and 1 can substitute for v.
![x^6-1=(x+1)(x^2-x(1)+1^2)(x-1)(x^2+x(1)+1^2)\\x^6-1=(x+1)(x^2-x+1)(x-1)(x^2+x+1)](https://tex.z-dn.net/?f=x%5E6-1%3D%28x%2B1%29%28x%5E2-x%281%29%2B1%5E2%29%28x-1%29%28x%5E2%2Bx%281%29%2B1%5E2%29%5C%5Cx%5E6-1%3D%28x%2B1%29%28x%5E2-x%2B1%29%28x-1%29%28x%5E2%2Bx%2B1%29)
We can repeat this for
, as 64 is just 2 to the sixth power.
![x^6-64=(x+2)(x^2-x(2)+2^2)(x-2)(x^2+x(2)+2^2)\\x^6-64=(x+2)(x^2-2x+4)(x-2)(x^2+2x+4)](https://tex.z-dn.net/?f=x%5E6-64%3D%28x%2B2%29%28x%5E2-x%282%29%2B2%5E2%29%28x-2%29%28x%5E2%2Bx%282%29%2B2%5E2%29%5C%5Cx%5E6-64%3D%28x%2B2%29%28x%5E2-2x%2B4%29%28x-2%29%28x%5E2%2B2x%2B4%29)